Preface - Boury-Esnault, Nicole (Zootaxa, 2018)
A volume on Atlantic-Mediterranean deep-sea and cave sponges dedicated to Klaus Rützler and Jean Vacelet to celebrate the publication, sixty years ago, of the first works on the biodiversity of marine caves (Laborel & Vacelet 1958; Russ & Rützler 1959).